2019
DOI: 10.4028/www.scientific.net/msf.969.787
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Abrasive Wear Behaviour of Waste Silk Fiber Reinforced Epoxy Biocomposites Using Taguchi Method

Abstract: The aim of this research article is to study the static mechanical properties and abrasive wear behavior of epoxy biocomposites reinforced with different weight percentage of waste silk fibers. The effect of parameters such as velocity (A), load (B), fiber loading (C) and abrading distance (D) on abrasive wear has been considered using Taguchi's L25 orthogonal array. The objective is to examine parameters which significantly affect the abrasive wear of biocomposites. The addition of silk fiber has resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The wear-resistant is boosted by the thorn powder. Results for several polymer-based composite fillers have been published by others [ 14 , 15 , 32 , 33 ]. The interaction plot for the lowest wear rate can be seen in Figure 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wear-resistant is boosted by the thorn powder. Results for several polymer-based composite fillers have been published by others [ 14 , 15 , 32 , 33 ]. The interaction plot for the lowest wear rate can be seen in Figure 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The wear resistance has been modified by the chemical treatment [ 14 ]. They observed that the abrading distance was the most important element in determining the wear of waste silk fiber-reinforced epoxy composites [ 15 ], followed by the loading of fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The present investigation reveals that the statistical as well as physical significance of the abrasive wear variables and their related interactions (percentage contribution > error) in abrasive wear properties of the fibres are subsequently sheared and later pulled out hybrid nanocomposites. ANOVA results show that fewer interactions are statistically significant but are not physically significant as the corresponding error is greater than the % contribution from the two interactions [34]. This method attributes the fluctuation of variance as well as averages to the absolute values evaluated throughout the experimental runs instead of the parameter's unit value.…”
Section: Worn Surface Morphologymentioning
confidence: 99%
“…Results showcased the increase in resistance of the composite against wear due to the incorporation of 5 wt% of graphite within the composites. [36] Evaluation of wear behavior in dry sliding condition for the sisal fibers/cashew nut shell liquid composites indicated that the specific wear resistance and CoF were improved. [37] The wear performance of jute fiber composites in dry condition was optimized using the Taguchi technique, and the results rendered minimum wear rate at a sliding distance of 1000 m, velocity of 1 m/s, and a load of 10 N. [38] Experimental studies on waste silk reinforced polyester composites for their tribological and mechanical characteristics were carried out, and from the results, it was understood that optimal wear was obtained for the process parameter combination of 10% reinforcement content, 500 m distance of abrasion, 25 N load, and 0.5 m/s velocity.…”
Section: Introductionmentioning
confidence: 99%